2018
DOI: 10.3233/bmr-170950
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of self-reported functional scores and thickening of quadriceps and femoral intercondylar cartilage under ultrasonography after single intra-articular injection of a novel cross-linked hyaluronic acid in the treatment of knee osteoarthritis

Abstract: HYAJOINT Plus is effective both subjectively and objectively for 6 months and is safe as a treatment for KOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
4
5
0
2
Order By: Relevance
“…The features characterizing the therapeutic course studied herein likely depend on the rational timing of injections with LHA and CLHA, which might exploit and optimize the pharmacokinetic and pharmacodynamics properties of the two forms of HA, in such a way that this regimen results in affordable clinical efficacy and, ultimately, patients' satisfaction. Such an interpretation is in keeping with other and independent evidences indicating that the pharmacodynamic features of HA may profoundly vary as a function of size, structure and chemical modifications (7,9,10,29). These results implicitly suggest that combining different forms of HA such as novel cooperative hybrid complexes or sequential/timed administration of linear and crosslinked preparations as in our case -instead of administering a single, specific form -could recruit multiple and converging mechanisms exalting the pleiotropic nature of native HA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The features characterizing the therapeutic course studied herein likely depend on the rational timing of injections with LHA and CLHA, which might exploit and optimize the pharmacokinetic and pharmacodynamics properties of the two forms of HA, in such a way that this regimen results in affordable clinical efficacy and, ultimately, patients' satisfaction. Such an interpretation is in keeping with other and independent evidences indicating that the pharmacodynamic features of HA may profoundly vary as a function of size, structure and chemical modifications (7,9,10,29). These results implicitly suggest that combining different forms of HA such as novel cooperative hybrid complexes or sequential/timed administration of linear and crosslinked preparations as in our case -instead of administering a single, specific form -could recruit multiple and converging mechanisms exalting the pleiotropic nature of native HA.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the HA fragments, depending on their size, display different rheological properties and have been shown to either stimulate or inhibit inflammatory response in targeted cells and in diseased tissues, and to differently modulate the production of specific inflammatory mediators (5,6). In agreement with the notion of the size-and structure-dependent bioactivity of HA, hybrid preparations of low-and high-MW HA (7,8), crosslinked-HA (9) and hexadecylic-derivatized HA (10) show even further variations/ complexity in terms of pharmacodynamics as compared to the native, linear polymers. From the clinical point of view, according to a Cochrane Database Systematic Review analysis based on a significant number of controlled trials, it has been demonstrated that HA injections significantly reduce pain in knee osteoarthritis (11).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Of these, 57 included data for IA HA mono-injection 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. At the end, 28 studies were included,43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 whereas 29 studies were removed for 1 or several of the following reasons:Two studies were in combination with surgery: anterior cruc...…”
Section: Resultsmentioning
confidence: 99%
“…A partir de là, 57 articles contenaient des données de mono-injection d'AH IA 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. Au final, 28 essais ont été inclus,43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 tandis que 29 études ont été retirées pour une ou plusieurs des raisons suivantes:3 essais étaient associés à...…”
Section: Résultatsunclassified